The Influence of Transformational Leadership Style and Work Culture on Employee Performance Mediated by Pancasila Discipline Attitude at SMK Angkasa 1 Jakarta - Jandris Slamat Tambatua; Besar Agung Martono (Journal GoodWill, 2025)
This study investigates the influence of transformational leadership and work culture on employee performance, with Pancasila disciplinary attitude as a mediating variable at SMK Angkasa 1 Jakarta. Using a quantitative survey approach, data were collected from 47 employees through questionnaires and analyzed using Partial Least Squares (PLS) via Smart PLS 4. The analysis included validity, reliability, and hypothesis testing. The findings reveal that transformational leadership and work culture do not directly influence employee performance. However, Pancasila disciplinary attitude positively and significantly affects performance. While transformational leadership does not significantly affect disciplinary attitude, work culture does. Furthermore, work culture indirectly improves employee performance through Pancasila discipline, while transformational leadership does not. These results suggest that strengthening a work culture aligned with Pancasila values—such as mutual cooperation and responsibility—is essential. Managerial recommendations include promoting a supportive culture, implementing fair discipline systems, modeling good behavior, encouraging active participation, and providing ongoing training and communication. This approach can enhance employee responsibility and performance within the school environment.